2021
DOI: 10.1101/2021.05.13.21257090
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

MiR-139-5p is a causal biomarker for type 2 diabetes; Results from genome-wide microRNA profiling and Mendelian randomization analysis in a population-based study

Abstract: MicroRNAs (miRNAs) have emerged as key regulators of gene expression. Differential expression of miRNAs has been linked to diabetes, but underlying pathways remain poorly understood. We performed genome-wide miRNAs profiling and tested the causal associations between miRNAs and type 2 diabetes in the general population. Subsequently, we investigated target genes and metabolites of miRNAs to provide insight into the metabolic disturbances that emerge with type 2 diabetes. Between 2002 and 2005, plasma levels of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 34 publications
1
3
0
Order By: Relevance
“…This miRNA has been reported by our group recently to be implicated in fatty liver disease [40]. At the same time, in the most recent publication with the Rotterdam Study data, we found the link between miR-193a-5p and incident of T2D [41]. These findings may indicate a potential role of miR-193a-5p in adiposity and metabolic pathways that warrant further experimental validation studies.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…This miRNA has been reported by our group recently to be implicated in fatty liver disease [40]. At the same time, in the most recent publication with the Rotterdam Study data, we found the link between miR-193a-5p and incident of T2D [41]. These findings may indicate a potential role of miR-193a-5p in adiposity and metabolic pathways that warrant further experimental validation studies.…”
Section: Discussionsupporting
confidence: 78%
“…In our search in previous studies on the association between the obesity-related miRNAs and cardiovascular and metabolic diseases, we found evidence for five miRNAs. Particularly, the top obesity-associated miRNA (miR-193a-5p), which has been shown by our group and others to be associated with hepatic steatosis and T2D [40,41]. In addition, the high expression of miR-145-5p has been a risk factor for essential hypertension [57].…”
Section: Discussionmentioning
confidence: 95%
“…Previous studies have identified miR‐193a‐5p to be positively correlated to BMI and to be upregulated in patients with obesity, diabetes, and nonalcoholic fatty liver disease. 89 , 90 , 91 Additionally, serum levels of miR‐193a‐5p have been shown to decrease in obese subjects following diet‐induced weight loss. 92 , 93 As miR‐193a‐5p is associated with insulin resistance parameters, the reduction of miR‐193a‐5p levels may serve to improve glucose metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, reverse causation can be avoided because genetic variants are assigned before the development of the disease (Davey Smith and Hemani, 2014). MR has been widely used to explore the causality between miRNAs and diseases, such as COVID-19 (Li et al, 2021), schizophrenia (Mu et al, 2023), lung cancer , incident acute coronary syndrome (Shen et al, 2021), and type 2 diabetes (Mens et al, 2021).…”
Section: Introductionmentioning
confidence: 99%